A police specialist rape investigation unit: a comparative analysis of performance and victim care - Rumney, Philip N. S. (Policing and society, 2020)
This article examines quantitative and qualitative data in an analysis of the workings of a specialist rape investigation unit and compares its performance with a non-specialist investigative approach. This is the first study to examine the work of a specialist rape investigation unit in this way. The research finds that the specialist unit outperformed the non-specialist investigative approach in many, though not all performance measures, including charging and ‘reached court’ rates in rape cases, retention of cases characterised by complex victim vulnerability, allocation of Sexual Assault Investigation Trained (SAIT) officers, rate of referral to Independent Sexual Violence Advisors (ISVA) and accuracy of crime recording. Further, police officer interview data suggest that team working and support, communication and a sense of common purpose were distinctive features of the specialist unit, when contrasted to experience of working in a non-specialist policing environment. These findings have policy and resource implications for the policing of rape and the need to achieve the best possible investigative standards in sexual offence cases, including the provision of appropriate care and addressing the needs of highly vulnerable victims. The article concludes by arguing that there is a growing body of evidence to suggest that investigative specialism is a crucial element in the police response to rape.